PENGARUH PELATIHAN TERHADAP KETERAMPILAN KADER POSYANDU DALAM MELAKSANAKAN TUGASNYA DI DESA BATUBULAN KANGIN - Ni Kadek Chilia Shilvia; I Ketut Kencana; I Made Suarjana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Health development is essentially the implementation of health efforts by the Indonesian people to achieve the ability to live healthy lives for the population in order to realize optimal community health degrees. Posyandu is a form of health service organized by the community with technical support from health workers. The purpose of this study was to assess the skills of Posyandu cadres related to their duties in the Batubulan Kangin Village. This type of research is Quasi Experiment. The population in this study were all posyandu cadres in Batubulan Kangin Village who were still active as cadres. The sample obtained was 45 posyandu cadres. Statistical tests using Wilcoxon. Age characteristics of samples 24-60 years. Distribution after weighing with enough categories was 40 people (88.9%), with good categories as many as 2 people (4.4%) and lacking categories as many as 3 people (6.7%). Distribution after recording with sufficient categories as many as 41 people (91.1%), with less categories as many as 4 people (8.9%). Distribution after counseling with sufficient categories was 29 people (64.4%), with good categories as many as 13 people (28.9%) and lacking categories as many as 3 people (6.7%). The results of the statistical test found that there was an effect of training on weighing skills, recording skills and extension skills.Keywords: Training, Experience, Formal Education